2023
DOI: 10.3390/toxics11070580
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Heavy Metals and Recent Advances in Their Removal: A Review

Manar K. Abd Elnabi,
Nehal E. Elkaliny,
Maha M. Elyazied
et al.

Abstract: Natural and anthropogenic sources of metals in the ecosystem are perpetually increasing; consequently, heavy metal (HM) accumulation has become a major environmental concern. Human exposure to HMs has increased dramatically due to the industrial activities of the 20th century. Mercury, arsenic lead, chrome, and cadmium have been the most prevalent HMs that have caused human toxicity. Poisonings can be acute or chronic following exposure via water, air, or food. The bioaccumulation of these HMs results in a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(37 citation statements)
references
References 174 publications
0
37
0
Order By: Relevance
“…This could threaten consumers of agricultural produce in the area, as the metal may be bioaccumulated. In high concentrations, Pb could lead to the breakdown of the central nervous system and other vital human organs, such as the liver and kidney, with children having been reported to be at high risk [ 54 ]. In all the studied soils, Pb exceeded the world soil average value of 27 mg/kg [ 31 ] except in NNP.…”
Section: Resultsmentioning
confidence: 99%
“…This could threaten consumers of agricultural produce in the area, as the metal may be bioaccumulated. In high concentrations, Pb could lead to the breakdown of the central nervous system and other vital human organs, such as the liver and kidney, with children having been reported to be at high risk [ 54 ]. In all the studied soils, Pb exceeded the world soil average value of 27 mg/kg [ 31 ] except in NNP.…”
Section: Resultsmentioning
confidence: 99%
“…Along with this, another crucial factor is the individual age as well as the method of exposure to the poison. Children's growing neurological systems are susceptible to lead poisoning and other heavy metal toxicity [57]. Similarly, the effects of nickel (Ni) are detrimental to human health.…”
Section: Heavy Metal Harmfulness Disturbs Human Healthmentioning
confidence: 99%
“…Furthermore, live mycelium, through biogeochemical processes, especially in the presence of compounds, such as chlorine and phosphorus, can biomineralize metallic lead into stable lead compounds, including oxalates, phosphates, and carbonates, at the hyphal surface. 25,26 These biomineralization pathways, along with crystal compositions and kinetics, are influenced by several environmental factors, including the concentration and oxidation state of the heavy metal, 27 composition of organic matter, 28 availability of other inorganic elements, 29 and the pH of the environment, 30,31 which assist the formation of stable compounds. For example, Aspergillus niger fungi, in a weakly acidic environment (pH ∼ 5.5), displayed an increased enzymatic phytase activity, leading to the hydrolysis of organic phosphorus into inorganic phosphates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These biopolymers present a variety of surface functional groups, including hydroxyl, amide, and carbonyl groups, which actively participate in the sorption of heavy metal ions via processes, such as electrostatic interactions, surface chelation, and ion exchange. Rudakiya et al showed that heavy metals, such as Cd 2+ , Cr 2+ , and mixed metals, were adsorbed by the biopolymers present on the hyphal cell wall of white rot (Phanerochaete chrysosporium) mushrooms, resulting in sorption efficiencies exceeding 90% across a wide range of pH values. Furthermore, live mycelium, through biogeochemical processes, especially in the presence of compounds, such as chlorine and phosphorus, can biomineralize metallic lead into stable lead compounds, including oxalates, phosphates, and carbonates, at the hyphal surface. , These biomineralization pathways, along with crystal compositions and kinetics, are influenced by several environmental factors, including the concentration and oxidation state of the heavy metal, composition of organic matter, availability of other inorganic elements, and the pH of the environment, , which assist the formation of stable compounds. For example, Aspergillus niger fungi, in a weakly acidic environment (pH ∼ 5.5), displayed an increased enzymatic phytase activity, leading to the hydrolysis of organic phosphorus into inorganic phosphates.…”
Section: Introductionmentioning
confidence: 99%